Metal-free and benign approach for the synthesis of dihydro-5′H-spiro[benzo[c]chromene-8, 4′-oxazole]-5′, 6(7H)-dione scaffolds as masked amino acids12. Issue 10 (18th April 2019) - Shafiee, Behnaz; Duffield, Joseph; Timm, Rudy; Liyanage, Rohana; Lay, Jackson O.; Khosropour, Ahmad R.; Amiri Rudbari, Hadi; Beyzavi, M. Hassan
Abstract : Eco-friendly one-pot synthesis of new masked amino acids is described. Abstract : An eco-friendly, straightforward, and three-component condensation/cascade reaction of 4-hydroxycoumarins and ( Z )-azlactones to construct diversified dihydro-5′ H -spiro[benzo[ c ]chromene-8, 4′-oxazole]-5′, 6(7 H )-diones as new masked amino acid derivatives has been developed with high to excellent yields and regio- and diastereoselectivity. This metal-free reaction proceeds via a one-pot cascade Michael addition/lactonization/decarboxylation reaction utilizing reusable propylene carbonate as a green solvent. The scale-up examination was also performed, showing high atom economy under the reaction conditions. Moreover, the mechanism of the reaction was further investigated using isotope-labeling, LC-MS monitoring, and TLC-MALDI-MS.